Functional capacity of patients with coronary artery disease at middle age - Khalida Alwan Mansour; Ali Kathum Jassem (Kufa Journal for Nursing Sciences)
Objectives: The study aims to identify the functional capacity for patients with coronary artery disease at middle age, and to find out the significant relation between functional capacity domains with variables patients gender, age, marital status, level of education, and income.